Responder analyses in randomised controlled trials for chronic low back pain: an overview of currently used methods - Henschke, Nicholas; van Enst, Annefloor; Froud, Robert; WG Ostelo, Raymond (European spine journal, 2014)
To provide an overview and a critical appraisal of the use of responder analyses in published randomised controlled trials (RCTs) of interventions for chronic low back pain (LBP). The methodology used for the analyses, including the justification, as well as the implications of responder analyses on the conclusions was explored.
Gesehen am 21.08.2020